2018
DOI: 10.18203/2320-1770.ijrcog20183782
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of elective hysterectomy cases in a tertiary care centre

Abstract: Background: Often hysterectomy remains the only option available in many gynaecological conditions, though it is resented by most women. This study aims to analyse the cases of hysterectomy performed in a tertiary care centre in India, with a view to modify and improve health care provided to women.Methods: A retrospective analysis of 500 cases of elective hysterectomy in Sree Gokulam Medical College and Research Foundation from January 2016 to December 2017 was done from hospital records. The observations acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In our study, the most common indication was dysfunctional uterine bleeding followed by leiomyoma. A study conducted by Prasad et al showed a 59.4% incidence of fibroid uterus in hysterectomy patients, the next common indication was abnormal uterine bleeding (23.3%) [ 14 ]. A study conducted by Sridevi et al showed they had 16% hysterectomies due to prolapse of the uterus, but in our study, it was only (4.4%].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most common indication was dysfunctional uterine bleeding followed by leiomyoma. A study conducted by Prasad et al showed a 59.4% incidence of fibroid uterus in hysterectomy patients, the next common indication was abnormal uterine bleeding (23.3%) [ 14 ]. A study conducted by Sridevi et al showed they had 16% hysterectomies due to prolapse of the uterus, but in our study, it was only (4.4%].…”
Section: Discussionmentioning
confidence: 99%
“…Hysterectomy is one of the most commonly performed surgeries in the world [1]. Indications for hysterectomies include common conditions like Abnormal uterine bleeding, fibroid, adenomyosis, endometrial lesions and less frequently tumors of female genital tract [2,3]. Types of hysterectomies done include subtotal hysterectomy, total abdominal hysterectomy with or without salphingoopherectomy, vaginal hysterectomy and laparoscopic method [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar age group was observed in other studies conducted by Sivapragasam V et al [8] In the present study the commonest indication for hysterectomy was symptomatic fibroid uterus in 142 cases (47.3%). Study done by Prasad DR et al showed a 59.4% incidence of fibroid uterus in hysterectomy patients [9] . Next common indication was abnormal uterine bleeding (23.3%).…”
Section: Discussionmentioning
confidence: 96%